NILAI-NILAI PENGHORMATAN TERHADAP LELUHUR DALAM TRADISI NYOBENG MASYARAKAT ADAT DAYAK BIDAYUH MENURUT PERSPEKTIF EMMANUEL LEVINAS - Andi, Andi Prayoga; Kardy (Universitas Hasanuddin, 2023)
The Nyobeng tradition is a tradition that has important values for the civilization of the Life of the Bidayuh Dayak tribe. This tradition arose because it was motivated by the many rituals that became the custom of the community to honor what their ancestors had done in ancient times. For the Bidayuh Dayak tribe, honoring the merits of the ancestors is a noble deed and must be maintained and continued for generations. The way to honor the merits of these ancestors is the Bidayuh Dayak tribe to carry out a custom known as